Dynamics of ozone and nitrogen oxides at Summit, Greenland: I. Multi-year observations in the snowpack. (December 2015) - Van Dam, Brie; Helmig, Detlev; Toro, Claudia; Doskey, Paul; Kramer, Louisa; Murray, Keenan; Ganzeveld, Laurens; Seok, Brian
Abstract: A multi-year investigation of ozone (O3 ) and nitrogen oxides (NOx ) in snowpack interstitial air down to a depth of 2.8 m was conducted at Summit, Greenland, to elucidate mechanisms controlling the production and destruction of these important trace gases within the snow. Snowpack O3 values ranged from 30 to 40 ppbv during winter months, and dropped below 10 ppbv in summer. Wintertime NOx levels were low at all depths in the snowpack (below 10 pptv for NO and below 25 pptv for NO2 ). In the summer, NO values up to 120 pptv, and NO2 mixing ratios up to ∼700 pptv were observed. O3 loss within the snowpack was observed throughout all seasons. The magnitude of the O3 loss rate tracked the seasonal and diurnal cycle of incoming short wave solar radiation. Production of NO within a shallow layer of the snowpack was recorded during the spring and summer months. NO2 production also occurred, and heightened levels were measured down to 2.5 m in the snowpack. The average daily maximum in NO was observed at solar noon, and the minimum was seen during night. The daily peak in NO2 was on average 7 h shifted from the incoming solar radiation and NO maxima. NOx levels in interstitial air during spring were enhanced relative to summer and fall. The influence of meteorological effects such as wind pumping on snowpack interstitial air levels of O3 and NOx was investigated using case study periods. Increased snowpack ventilation during high wind events was found to yield enhancement in snowpack NOx, with this effect being enhanced during times when O3 was elevated in ambient air. This behavior suggests that O3 is involved in NOx production in the snowpack. This extensive set of observations is used to re-evaluate physical and chemical processes that describe the dynamic O3 and NOx chemistry occurring within snowpack interstitial air at Summit. Highlights: Ozone and nitrogen oxides in air below and above the snow surface were continuously measured for two years. Concentrations of these gases show highly dynamic diurnal and seasonal dependencies. We found that NOx in snowpack air is higher at night, which contrasts previous understanding and model results.